2013
DOI: 10.1007/s11336-013-9386-5
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Correction to the Likelihood Ratio Statistic for Structural Equation Modeling with Many Variables

Abstract: Survey data typically contain many variables. Structural equation modeling (SEM) is commonly used in analyzing such data. The most widely used statistic for evaluating the adequacy of a SEM model is T ML, a slight modification to the likelihood ratio statistic. Under normality assumption, T ML approximately follows a chi-square distribution when the number of observations (N) is large and the number of items or variables (p) is small. However, in practice, p can be rather large while N is always limited due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…Moreover, as the models comprised a very large number of observed variables, in turn leading to inflated test-statistics (Herzog, Boomsma, & Reinecke, 2007;Moshagen, 2012), we additionally applied the correction proposed by Yuan, Tian, and Yanagihara (2015), yielding a test-statistic corrected for both the effects of non-normality and model-size (corresponding to…”
Section: Analysesmentioning
confidence: 99%
“…Moreover, as the models comprised a very large number of observed variables, in turn leading to inflated test-statistics (Herzog, Boomsma, & Reinecke, 2007;Moshagen, 2012), we additionally applied the correction proposed by Yuan, Tian, and Yanagihara (2015), yielding a test-statistic corrected for both the effects of non-normality and model-size (corresponding to…”
Section: Analysesmentioning
confidence: 99%
“…Further work on correcting Type I errors of these statistics is needed before studying their power properties. In this direction, Yuan, Tian, and Yanagihara () recently proposed a technique, termed empirical modelling, to correct the likelihood ratio statistic T ML with normally distributed data, where the multiplier n = N –1 in the composition of T ML is replaced by a formula calibrated using Monte Carlo simulation. The same idea can be used to correct the rescaled and adjusted statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Variations of this correction exist, but the one most studied ; see also Fouladi, 2000;Savalei, 2010) is a simplified correction proposed by Bartlett (1950) in the context of exploratory factor analysis. A more general correction is called the Swain correction (Swain, 1975), and even more corrections were described by Yuan, Tian, and Yanagihara (2015). Herzog, Boomsma, and Reinecke (2007) and Herzog and Boomsma (2009) compared these corrections and concluded that the Swain correction worked best; however, they only looked at complete and normal data.…”
Section: Improving the Chi-square Test Statisticmentioning
confidence: 99%
“…Herzog, Boomsma, and Reinecke (2007) and Herzog and Boomsma (2009) compared these corrections and concluded that the Swain correction worked best; however, they only looked at complete and normal data. Shi, Lee, and Terry (2018) also compared the various corrections in more realistic settings and concluded that the so-called "empirically" corrected test statistic proposed by Yuan et al (2015) generally yielded the best performance-particularly when fitting large structural equation models with many observed variables. Still, they warn that when the number of variables (P) in a model increases, the sample size (n) also needs to increase in order to control Type I error.…”
Section: Improving the Chi-square Test Statisticmentioning
confidence: 99%